METODE DEMONSTRASI UNTUK PENINGKATAN KEMAMPUAN MEMBACA PUISI SISWA KELAS VII SMP - Riefani Bima Anzalta; Hadi Wardoyo; Suryantoro (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to apply the demonstration method in learning to read poetry and improve the ability to read poetry of seventh grade students of Islamic Junior High School Donomulyo in the 2023/2024 academic year. Based on the results of observations, several obstacles were found in reading poetry, including lack of reading fluency, low interest in poetry, limited creativity of educators in choosing learning methods, weak student motivation, and difficulty in understanding proper poetry reading techniques. To overcome these problems, classroom action research (PTK) was implemented in two cycles with six meetings. The research stages included planning, action implementation, observation, and reflection. The research subjects consisted of 26 seventh grade students. This study found that the application of the demonstration method was able to improve students' ability to read poetry. This can be seen from the increase in the average with an initial score of 54.7% in cycle I (low category) to 86.4% in cycle II (good category). So it can be concluded that the demonstration method is effective in improving the ability to read poetry of seventh grade students of Islamic Junior High School Donomulyo.